If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 90 = 9(m + 2.4) Reorder the terms: 90 = 9(2.4 + m) 90 = (2.4 * 9 + m * 9) 90 = (21.6 + 9m) Solving 90 = 21.6 + 9m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-9m' to each side of the equation. 90 + -9m = 21.6 + 9m + -9m Combine like terms: 9m + -9m = 0 90 + -9m = 21.6 + 0 90 + -9m = 21.6 Add '-90' to each side of the equation. 90 + -90 + -9m = 21.6 + -90 Combine like terms: 90 + -90 = 0 0 + -9m = 21.6 + -90 -9m = 21.6 + -90 Combine like terms: 21.6 + -90 = -68.4 -9m = -68.4 Divide each side by '-9'. m = 7.6 Simplifying m = 7.6
| 3-x-(-5)+x=2x+(-3) | | 2e^2x-6x-2=0 | | 2-x-4+4x=x+5 | | 7x-8x=8x+10-8x | | 8.7b-.4=17 | | 2x+x+-x+(-1)=7+2-x | | 2x-5=-2x | | .13y-.6=.83 | | .8d+.4=.96 | | Log(6x-4)=3 | | b-0.14b= | | 3-x+2=-10+x | | 3x+2=-10+x | | 7-4y=18 | | 4428=41(p+20) | | x^2+dx+1=0 | | 4428=20p+41 | | 2lg(2x+1)=LG(x+11) | | 3m-7=mp+7 | | (3x)y+(4x+5y)= | | (25+p)47=4465 | | -11+24+(-32)= | | -11+23+(-32)= | | y=3x^2+6x-105 | | x+(x*1.8)+(x*0.8)=18 | | y=7x^2-16x+4 | | x+66=22x | | 9m^2-40m+16=0 | | 7x+2=98 | | 1/2×-8=-6 | | 1904=34(p+15) | | (15+p)34=1904 |